2021
DOI: 10.1063/5.0039264
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of plasma-driven decomposition of per- and polyfluoroalkyl substances (PFAS) in raw contaminated ground water

Abstract: Per- and polyfluoroalkyl substances (PFAS) are contaminants of emerging concern owing to their ability to bioaccumulate in the body and subsequently cause cancer. PFAS, while recalcitrant to advanced oxidation, can be degraded by plasma action. In this work, we investigate the efficacy of two plasma reactors on degrading PFAS in ground water derived from two different contaminated sites. The reactors included an array of underwater plasma jets and a dielectric barrier discharge (DBD) with water dielectric barr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…The EE/O value for RO reject water is one order of magnitude lower than that for the treatment of leachate (20–36 kWh/m 3 ) and two orders of magnitude lower than that for IX still bottom (380–830 kWh/m 3 ), respectively. Other studies reported the energy demand for the treatment of PFOA and PFOS to be 241 kWh/m 3 in a dielectric barrier discharge plasma jet system and 237 kWh/m 3 in a reverse vortex flow gliding arc plasma system, , which is comparable with our studies. The wide range of EE/O values for plasma technology (1.7–830 kWh/m 3 ) might be due to the water matrix, PFAS initial concentration, and experimental setup, among other factors.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The EE/O value for RO reject water is one order of magnitude lower than that for the treatment of leachate (20–36 kWh/m 3 ) and two orders of magnitude lower than that for IX still bottom (380–830 kWh/m 3 ), respectively. Other studies reported the energy demand for the treatment of PFOA and PFOS to be 241 kWh/m 3 in a dielectric barrier discharge plasma jet system and 237 kWh/m 3 in a reverse vortex flow gliding arc plasma system, , which is comparable with our studies. The wide range of EE/O values for plasma technology (1.7–830 kWh/m 3 ) might be due to the water matrix, PFAS initial concentration, and experimental setup, among other factors.…”
Section: Resultssupporting
confidence: 90%
“…We have recently conducted a series of plasma degradation studies investigating the removal of PFAS from highly conductive and complex water matrices including landfill leachate and IX still bottoms using an enhanced contact (EC) plasma reactor. , In this type of reactor, argon is bubbled through a diffuser that transports long-chain PFAS to the gas–liquid interface where they are degraded by plasma-generated species. Solvated electrons, argon ions, and hot electrons have all been proposed to be responsible for the degradation of PFAS molecules . Our results indicate that for a range of aqueous matrices, long-chain PFAS (C ≥ 6 for perfluoroalkyl sulfonates (PFSAs) and C ≥ 8 for perfluoroalkyl carboxylates (PFCAs)) at typical groundwater concentrations (ng/L to μg/L) can typically be 90% degraded within minutes of treatment.…”
Section: Introductionmentioning
confidence: 98%
“…These results hint that 2 mA may correspond to too low of a current density (4 mA/cm 2 ) and reaction rate for the BDD, and in the future, electrodes must be designed with better matching of power density. That is, either smaller areas for the BDD or, preferably, larger currents spread over a large area for the plasma are needed …”
Section: Resultsmentioning
confidence: 99%
“…That is, either smaller areas for the BDD or, preferably, larger currents spread over a large area for the plasma are needed. 52 Role of Short-Lived Reactive Species. Although the split cell experiments indicated that both working electrodes can effectively degrade PFOA, where the plasma is assisted by the counter electrode, additional experiments are necessary for comparing major degradation pathways.…”
Section: Langmuirmentioning
confidence: 99%
See 1 more Smart Citation